Report on the 17th International Scientific Conference in the “Humanistic Ecology” Series: “Environmental Philosophy and Ethics in the Face of the Ecological Crisis” (Warsaw, 20-21 September 2023) - Ryszard F. Sadowski (Studia Ecologiae et Bioethicae)
SEeB does not provide abstracts for reports.